Plasmacytoid urothelial carcinoma: a case of histological variant of urinary bladder cancer with aggressive behavior - Leonardo Gomes da Fonseca; Ciro Eduardo Souza; Romulo Loss Mattedi; Daniel Motta Girardi; Álvaro Sadek Sarkis; Paulo Marcelo Gem Hoff (University of São Paulo, 2014)
Plasmocytoid variant urothelial carcinoma (PVUC) of the urinary bladder is a rare histological variant of transitional cell carcinoma. Data regarding PVUC shows that this neoplasia presents a distinctive clinical outcome represented by aggressive behavior and poor survival rate. The authors report a case of a 57-year-old male patient with a 3-month history of hematuria and pelvic pain. Radical cystectomy with lymphadenectomy was performed and pathological examination showed a pT3pN0 PVUC of the bladder. The patient remained free of recurrence for 8 months, but the disease recurred involving the abdominal wall and subcutaneous tissue. Chemotherapy provided a positive clinical response and relief of symptoms. The authors call attention to the aggressiveness of this rare variant of bladder cancer and recommend radical surgery and multidisciplinary management of this neoplasm.